Bentuk dan nilai rasa disfemia pada komentar netizen dalam bermedia sosial di instagram - HL, Nur Ihsan (Universitas Lampung, 2023)
There were several language terms used by Instagram users for exacerbating the lexical units meaning, leading to reader negative impressions. This research was focused on Instagram social media data that can be accessed as friends and in general. This research was different from previous research because most focus on one Instagram account. This research has two main objectives. First, to find out the form of dysfemia in the Instagram comment column. Second, to find out the value of dysfemia contained in the comments. This research type was qualitative with the method of content analysis. For this purpose, data was collected from all forms of netizen interactions, including comments on words, phrases and expressions. Meanwhile, the source of the research data was the conversations of Instagram users. The research instrument used was the researcher himself and a number of supporting equipment including cell phones and stationery (books and pens) were also used. Data was collected through reading and recording techniques. Then the collected data was analyzed through reduction, presentation, and drawing conclusions. The results of the study showed that the forms of dysphemia in the comments of Instagram users tend towards dyspnea in the form of words, phrases and expressions. Meanwhile, the value content of taste was scary, scary, disgusting, and strengthening. Future studies should compare dyspnea with euphemia.Keywords: Form, dyspnea, Instagram, netizen, sense value